Versatile polyiodopyrazoles: synthesis and biocidal promise. Issue 16 (27th January 2015) - Chand, Deepak; Shreeve, Jean'ne M.
Abstract : An efficient synthetic route provides ready access to polyiodopyrazoles, including 3, 4, 5-triiodopyrazole; further introduction of the diiodo-methyl group increases the iodine concentration which gives rise to anti bioagent detonation products I2 and HI, making these iodo compounds promising candidates as ingredients in agent defeat weapons (ADWs). Abstract : An efficient route to polyiodopyrazoles, 3, 4, 5-triiodopyrazole (1 ), 1-methyl-3, 4, 5-triiodopyrazole (2 ) and 1-diiodomethyl-3, 4, 5-triiodopyrazole (3 ), opens the door to prospective biocides. Nitration of1 and2 gives the previously inaccessible compounds, 3, 4-dinitro-5-iodopyrazole (4 ), and 3, 4-dinitro-5-iodo-1-methylpyrazole (5 ), respectively. These synthetic pathways will open many fronts for pyrazole chemistry.